Early plant development depends on embryo damage location: the role of seed size in partial seed predation - Perea, Ramón; Fernandes, G. Wilson; Dirzo, Rodolfo (Oikos, 2020)
Seed predators sometimes inflict non‐lethal seed damage. We asked whether seed size modulates the location of insect seed damage and examined whether location‐specific damage on the embryo influences early plant development (embryo survival, germination, seedling emergence and performance). We used intact and weevil‐infested seeds of a prevalent California oak tree Quercus agrifolia as study model. We conducted observational and manipulative studies (simulate partial embryo damage). Seed size significantly affected the location of insect damage within the seed and, in turn, the probability of embryo damage, with larger seeds showing lower probability of embryo damage. The location of the larva exit hole was strongly associated with the probability of embryo damage, with 0.9 probability when the exit hole is located <5 mm from the embryo. Partial damage on the embryo was found in ca 11% of the infested seeds (n = 250). Among them, 63% showed damage only on the inner part (plumule) of the embryo. Damage on the plumule (the rudimentary shoot) was more lethal than damage on the radicle, particularly at the emergence phase, when success rate of plumule‐damaged seeds decreased by half as compared to that of radicle‐damaged seeds. Plumule‐damaged seeds also emerged much later and performed more poorly than radicle‐damaged seeds. Furthermore, seedlings that emerged from plumule‐damaged seeds showed poorer physiological parameters (lower chlorophyll and nitrogen content) than those emerged from radicle‐damaged seeds. Overall, intact seeds performed better than both types of damaged seeds. We highlight that seed size and its associated differential location of seed damage determines the occurrence of embryo damage and the region affected within the embryo (e.g. plumule versus radicle) which, in turn, affects important components of plant fitness. Different selective pressures affecting mostly the plumule (insects) versus the radicle (embryo‐clipping rodents) may contribute to elucidate the co‐evolutionary dynamics of seeds and their predators.